Gen Z Teacher Transformation : Self-Development Strategy to Improve Social and Personality Competence - Utami, Widya; Santosa, Achadi Budi; Suyatno, Suyatno (Universitas Pendidikan Mandalika, 2025)
This study aims to reveal the transformation of Gen Z teachers by highlighting the problem of improving social and personality competencies and identifying the strategies they use. This research used a qualitative approach with a case study method. Data collection was carried out using in-depth interview techniques with five Gen Z teachers in Lubuklinggau City who were selected using purposive sampling. The data analysis technique uses the Miles and Huberman model which includes the stages of data collection, data reduction, data presentation, and conclusions. The findings of this study reveal that Gen Z teachers face problems such as lack of self-awareness, dependence on technology, minimal training, and limited time and workload. As a result, Gen Z teachers are at risk of experiencing gaps in communication skills and emotional intelligence, being less prepared to face challenges involving collaboration in the workplace, and in their social lives. The strategies used by Gen Z teachers in their social and personality development include self-assessment, self-development, and utilization of technology. They also continue to learn and adapt in developing their personality and social interactions, in order to improve the quality of their teaching and social relationships.